A simulation supply chain model for a sustainable and environment friendly poultry industry: Insights from Bangladesh - Shamsuddoha, M.; Klass, Desmond; Quaddus, Mohammed (ANZAM, 2011)
The focuses on environment and reverse supply chain have increased in recent years among academic and industry circle. Yet, Bangladesh poultry is to achieve environmental sustainability in her extended forward and reverse supply chain. In this paper, supply chain model developed based on a case poultry industry. Design science and case method under positivist and quantitative paradigm followed to develop simulation model using simul8 application to fit the real poultry case. The objectives of this paper are to review literature, develop simulation supply chain model and later tested it through historic data. The results briefly discussed and model capturing the relationship among forward, reverse and mainstream supply chain of the case. Different random trial runs of the simulation model have shown in the result section to find out optimality.